2015
DOI: 10.1590/s1517-97022015041858
|View full text |Cite
|
Sign up to set email alerts
|

El conocimiento pedagógico del contenido de estadística en profesores de primaria

Abstract: En este estudio desarrollamos un cuestionario sobre el saber del profesor de primaria en su conocimiento disciplinario de estadística y en su conocimiento para llevar a cabo la enseñanza de la estadística, centrado en el conocimiento del profesor en relación al saber estadístico del alumno y la enseñanza del contenido estadístico. Se incluyeron tres elementos de la educación estadística: comprensión gráfica, diferenciación de niveles cognitivos y comprensión generada al cambiar de sistemas de representación. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
0
15
0
15
Order By: Relevance
“…Piaget and Inhelder ( 1955 ) argued that some types of tables should be presented to students who are at least 12 years old. In 2010, two Chilean studies, (Estrella, 2010 ;Estrella, Olfos & Mena-Lorca, 2015 ) referred to pedagogical content knowledge, showed that treatment of tables presents diffi culties for teachers ( n = 85) and students ( n = 1500). What concepts are present in students' mind during their interpretation of tables?…”
Section: Discussionmentioning
confidence: 99%
“…Piaget and Inhelder ( 1955 ) argued that some types of tables should be presented to students who are at least 12 years old. In 2010, two Chilean studies, (Estrella, 2010 ;Estrella, Olfos & Mena-Lorca, 2015 ) referred to pedagogical content knowledge, showed that treatment of tables presents diffi culties for teachers ( n = 85) and students ( n = 1500). What concepts are present in students' mind during their interpretation of tables?…”
Section: Discussionmentioning
confidence: 99%
“…Para ambos tipos de profesores, no hay cursos de didáctica de la estadística. La situación internacional al respecto es parecida (ESTRELLA, 2016;OLFOS;MENA-LORCA, 2015).…”
Section: Los Profesores Evaden Algunos Contenidosunclassified
“…Although scholarship on different embodiments of MKT is vast, there also exists research on the understanding of SKT. SKT became a subject of research projects with in-service teachers outside of the United States (Burgess 2007(Burgess , 2009a; Estrella, Olfos, & Mena-Lorca, 2015;Watson, 2001;Watson, Callingham, & Donne, 2008;Watson & Nathan, 2010) as well as research done with preservice teachers (PSTs) in the United States (Groth, 2014). Much of the research on SKT with in-service teachers outside of the United States is concentrated around Australia with Watson and colleagues (Watson, 2001;Watson et al, 2008;Watson & Nathan, 2010), who have developed, and validated, different assessments in understanding teacher knowledge including pedagogical content knowledge (PCK) (Hill, Ball, and Schilling, 2008) within statistics.…”
Section: Statistical Education Of Teachersmentioning
confidence: 99%
“…Much of the research on SKT with in-service teachers outside of the United States is concentrated around Australia with Watson and colleagues (Watson, 2001;Watson et al, 2008;Watson & Nathan, 2010), who have developed, and validated, different assessments in understanding teacher knowledge including pedagogical content knowledge (PCK) (Hill, Ball, and Schilling, 2008) within statistics. Another contribution to the research with in-service teachers has come from Estrella, Olfos, and Mena-Lorca (2015) in Chile, who also created an instrument to measure PCK that focuses on teachers' awareness of student statistical knowledge.…”
Section: Statistical Education Of Teachersmentioning
confidence: 99%
See 1 more Smart Citation